2013
DOI: 10.1371/journal.pone.0077062
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Liaoning Cashmere Goat Transcriptome: Sequencing, De Novo Assembly, Functional Annotation and Comparative Analysis

Abstract: BackgroundLiaoning cashmere goat is a famous goat breed for cashmere wool. In order to increase the transcriptome data and accelerate genetic improvement for this breed, we performed de novo transcriptome sequencing to generate the first expressed sequence tag dataset for the Liaoning cashmere goat, using next-generation sequencing technology.ResultsTranscriptome sequencing of Liaoning cashmere goat on a Roche 454 platform yielded 804,601 high-quality reads. Clustering and assembly of these reads produced a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
3
7
0
2
Order By: Relevance
“…Since annotated reference sequence of Capra hircus is unavailable, an integrated, non-redundant and well-annotated reference sequence of Bos taurus was used for further analysis. Bos taurus reference genome was earlier used for comparative analysis and functional annotation of goat transcriptome by several groups [ 15 - 17 ]. Also, the average sequence identity between these two species was estimated to be 82.79%.…”
Section: Methodsmentioning
confidence: 99%
“…Since annotated reference sequence of Capra hircus is unavailable, an integrated, non-redundant and well-annotated reference sequence of Bos taurus was used for further analysis. Bos taurus reference genome was earlier used for comparative analysis and functional annotation of goat transcriptome by several groups [ 15 - 17 ]. Also, the average sequence identity between these two species was estimated to be 82.79%.…”
Section: Methodsmentioning
confidence: 99%
“…Capra hircus genome is not well annotated therefore the well-defined B. taurus reference genome was used for mapping reads using TopHat version 2.0.7 (Kim et al, 2013). Bos taurus reference genome has been previously used by many groups for analyzing the goat transcriptome (Liu et al, 2013;Fontanesi et al, 2010). The mapped reads were then assembled using cufflinks, which quantifies the gene expression in terms of FPKM.…”
Section: Viral Transcript Quantificationmentioning
confidence: 99%
“…In recent years, the characteristics of cashmere fiber have received special attention in that they play an obvious role in cashmere quality. Several studies indicated that coding and noncoding genes were associated with the regulation of cashmere growth [3][4][5] . In addition, several important pathways have been demonstrated to be related to the formation of cashmere fiber [6][7][8] , for instance, Wnt, NF-κB, Shh, Notch and other signaling pathways [9][10][11][12][13] .…”
mentioning
confidence: 99%